UNDERSTANDING AGGRESSION IN CHILDREN AND ADOLESCENTS: A COMPREHENSIVE BIBLIOMETRIC STUDY OF GLOBAL RESEARCH TRENDS AND KEY CONTRIBUTIONS - Zulfa Saleh; Syed Mohamad Syed Abdullah (Journal of Contemporary Social Science and Education Studies (JOCSSES) E-ISSN- 2785-8774, 2024)
This bibliometric study provides a comprehensive analysis of research trends, key contributors, and international collaboration in the field of aggressive behavior among children and young people from 2020 to 2024. Utilizing VOS viewer for network visualization and Publish or Perish software for data extraction and analysis, this study examines publication patterns, identifying a period of stability from 2020 to 2022, followed by a significant decline in 2024, suggesting shifts in funding and research priorities. Key authors such as T.R. Nansel and Hong, J.S., emerge as influential figures, with their work extensively shaping the field. Top journals, including the Journal of Interpersonal Violence and Frontiers in Psychology, highlight evolving research interests, particularly in developmental stages, bullying, mental health, and trauma. The study also reveals a robust network of international collaboration, with the United States, the United Kingdom, China, Germany, and Italy at the forefront, and emerging contributions from countries like Malaysia and Nigeria. This analysis underscores the necessity for adaptive, multidisciplinary approaches and continued global partnerships to address the complex challenges of youth aggression and violence effectively. The findings provide valuable insights into the current state and future directions of research, guiding policymakers, practitioners, and researchers in their efforts to mitigate aggressive behavior in youth.